Bahay Kubo, the vegetable story An encouragement approach on vegetable consumption towards a healthier and balanced diet - Guingona, Kara Marie V. (2013)
The Filipinos eating habits have been changing poorly for the past decades. In this era of fast foods and instant foods, recent studies show that Filipinos are eating less and less vegetables in their diets. Filipinos having an unbalanced diet contribute to the rising cases of Malnutrition in the Philippines today. Lifelong eating habits are shaped early. Nutrition and the practice of healthy food consumption are very important during childhood because it is directly linkied to all aspects of growth and development as adults in the future. Albert Bandura's Social Learning theory has been identified as one of the most successful frameworks in understanding human behavior. Using this theory, in relation with the current nutritional status of Filipinos, the purpose of this study is to determine and further explore on Filipino's lifestyle and perception to healthy food consumption. The study also sought ot find and effective solution in alleviating the rise of malnutrition in the Philippines today. From a survey that was conducted to 200 respondents in various elementary schools, the power and influence of multimedia and role models in our society, (cradled by Albert Bandura's Theory of Learning), was supported by result of the survey that was conducted. The highest vote went to television viewership being the most enjoyed activity among Filipino children today.
"April 2013"
Thesis (BFA)--University of the Philippines Diliman
Keywords: Children -- Nutrition; Food habits -- Philippines; Graphic arts